Charge Transport in High‐Mobility Field‐Effect Transistors Based on Inkjet Printed Random Networks of Polymer Wrapped Single‐Walled Carbon Nanotubes. (27th October 2020) - Scuratti, Francesca; Salazar‐Rios, Jorge Mario; Luzio, Alessandro; Kowalski, Sebastian; Allard, Sybille; Jung, Stefan; Scherf, Ullrich; Loi, Maria Antonietta; Caironi, Mario
Abstract: Printed random networks of polymer‐wrapped multi‐chiral semiconducting carbon nanotubes (s‐SWCNTs) are an opportunity for mass‐manufacturable, high‐performance large‐area electronics. To meet this goal, a deeper understanding of charge‐transport mechanisms in such mixed networks is crucial. Here, charge transport in field‐effect transistors based on inkjet‐printed s‐SWCNTs networks is investigated, obtaining direct evidence for the phases probed by charge in the accumulated channel, which is critical information to rationalize the different transport properties obtained for different printing conditions. In particular, when the fraction of nanotubes with smaller bandgaps is efficiently interconnected, the sparse network provides efficient charge percolation for band‐like transport, with a charge mobility as high as 20.2 cm 2 V −1 s −1 . However, when the charges are forced by a less efficient morphology, to populate also higher bandgap nanotubes and and/or the wrapping polymer, thermally activated transport takes place and mobility drops. As a result, a trade‐off between network density and charge transport properties is identified for device current optimization, in both p‐ and n‐type regimes. These findings shed light on the fundamental aspects related to charge transport in printed s‐SWCNT mixed networks and contribute to devise appropriate strategies for the formulation of inks and processes towards cost‐effective mass production schemes of high‐performance large‐area electronics. Abstract : This work provides direct evidence of how charge in the channel of field‐effect transistors selectively probes the distribution of energy gaps in inkjet‐printed random networks of mixed semiconducting carbon nanotubes. The mechanisms of charge transport versus the processing parameters are rationalized, identifying a non‐obvious trade‐off between network density and charge transport properties for optimization of device performance.